Communication for the Handicapped in College An Annotated List of References and Aids - Gust, Tim, Comp.; Pittsburgh Univ., PA. Research and Training Center in Vocational Rehabilitation ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
The material and references that follow are concerned with communication needs of the handicapped student in college. References concerning studies and surveys about the use of certain communication aids; listings of suppliers of aids, talking books, and large print books; as well as articles dealing with more general information having reference to communication problems of the handicapped student are included. (Author)
Sponsoring Agency: Social and Rehabilitation Service (DHEW), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; College Students; Communication Problems; Handicapped Students